Tolerance induction to a hapten protein conjugate in vivo: are suppressor T cells involved. - Huchet, R; Feldmann, M (1974)
The cellular basis of high and low zone tolerance to dinitrophenylated human IgG (DNP HGG) was investigated in mice by using an analysis of carrier hapten relationships to identify the nonresponding cell. Low zone tolerance in vivo was found to be solely due to tolerance at the T cell level, confirming the previous work of Mitchison and Rajewsky. High zone tolerance, after a single injection of 10 mg of deaggregated DNP HGG was due to essentially complete T cell tolerance. It was also due to partial B cell tolerance in the intact host. The degree of B cell tolerance was much more marked if tested in vitro than in vivo, and for IgG antibody rather than IgM. The mechanism of high zone tolerance induction was analyzed. 2 and 3 days after antigen injection there was a transient appearance of T cells which, in the presence of the tolerogen, specifically suppressed DNP reactive B cells in vitro. The significance of these specific suppressor T cells in the mechanism of high zone tolerance induction is discussed.